1999
DOI: 10.1021/jo9903609
|View full text |Cite
|
Sign up to set email alerts
|

Amino(hetero)arylmethylation of Phenols with N-[α-Amino(hetero)arylmethyl]benzotriazoles

Abstract: N- [R-Amino(hetero)arylmethyl]benzotriazoles derived from a variety of (hetero)aromatic aldehydes were reacted with sodium phenolates to afford amino(hetero)arylmethylated phenols in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Although the Mannich bases of 2-naphthols with heterocyclic amines were reported in the past (24, 26, 27, 51), their detailed NMR behavior has not been examined, to the best of our knowledge; some NMR peaks are reported in broad range (27). We consistently noted interesting NMR activities of the compounds under investigation, as they often gave poorly resolved heterocyclic proton and carbon peaks in their respective spectra at ambient temperature.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Although the Mannich bases of 2-naphthols with heterocyclic amines were reported in the past (24, 26, 27, 51), their detailed NMR behavior has not been examined, to the best of our knowledge; some NMR peaks are reported in broad range (27). We consistently noted interesting NMR activities of the compounds under investigation, as they often gave poorly resolved heterocyclic proton and carbon peaks in their respective spectra at ambient temperature.…”
Section: Resultsmentioning
confidence: 61%
“…The first synthesis of racemic Mannich bases of 2-naphthol was achieved by Betti (18)(19)(20)(21)(22) at the turn of the 20th century. Thereafter, numerous modifications of this reaction surfaced (23)(24)(25)(26)(27) and optically pure Betti base analogs were prepared either by resolution or by the induction of chirality by the use of optically active amines (11-17, 28, 29).…”
Section: Introductionmentioning
confidence: 99%
“…Katritzky et al 3 have reported an improved aminoalkylation of 2-naphthol and phenol derivatives with prefor med iminium salts derived from aromatic aldehydes, in a two-step sequence with 26%-92% yields. Moreover, aminoalkylation of electron rich aromatic compounds such as 2-naphthol for the synthesis of Betti base derivatives [4][5][6][7][8][9][10][11][12][13][14] in the presence of LiClO 4 , Sc(OTf) 3 , Yb(OTf) 3 , La(OTf) 3 , YbCl 3 , TiCl 4 and Me 3 SiCl as catalysts has been reported. [15][16][17] The racemic aminonaphthols (Betti bases) have been used for transformation into products with anti bacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…The first synthesis of racemic Mannich-bases of 2-naphthol was achieved by Betti at the turn of the twentieth century. 4 Thereafter numerous modifications of this reaction surfaced [5][6][7][8][9][10] . Since these compounds have multiple centers for chelation with metal ions, they are likely to be potent inhibitors of metallo-enzymes 11,12 .…”
mentioning
confidence: 99%